Perancangan Arsitektur Enterprice Pada Madrasaah Tahiliyah Menggunakan Metode Togaf ADM - Hijrah Hijrah; Afcahrina Diniyil M; Akhlis Munazilin (Jurnal Riset Teknik Komputer, 2026)
Madrasah Ta’hiliyah Putri, as a faith-based educational institution, requires a structured and integrated management of academic and administrative processes to support the effectiveness of educational services. However, the existing information systems are still partial and not fully aligned with the organizational needs. This study aims to design an enterprise architecture for Madrasah Ta’hiliyah Putri using The Open Group Architecture Framework Architecture Development Method (TOGAF ADM). The research method follows several phases: preliminary, architecture vision, business architecture, information system architecture, technology architecture, and opportunities and solutions. The results of this study produce an enterprise architecture design encompassing business architecture, data architecture, application architecture, and technology architecture aligned with the vision and mission of Madrasah Ta’hiliyah Putri. This design is expected to serve as a guideline for developing an integrated information system, enhancing the efficiency of academic and administrative management, and supporting more precise and sustainable management decision-making.